If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x = 9 + -8x Solving 8 + -3x = 9 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 8 + -3x + 8x = 9 + -8x + 8x Combine like terms: -3x + 8x = 5x 8 + 5x = 9 + -8x + 8x Combine like terms: -8x + 8x = 0 8 + 5x = 9 + 0 8 + 5x = 9 Add '-8' to each side of the equation. 8 + -8 + 5x = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = 9 + -8 5x = 9 + -8 Combine like terms: 9 + -8 = 1 5x = 1 Divide each side by '5'. x = 0.2 Simplifying x = 0.2
| 9Xx(-Xy)= | | 2(3+2x)-5=25 | | 4-6x=2x+3 | | 8-7x=53-42x | | .75+d=-.5 | | 28+m=-39 | | 50-g=47 | | 2x+7+8x+3= | | -13+t=-27 | | 8x+13y+50=180 | | m-18=-13 | | 35-4x=5x+22 | | 2(2x+1)=3x+9 | | y^2+6y-4=0 | | x^2+x^2=32 | | 2x-10=-45-9x | | 130-3x=6x+13 | | 4[3-3(x+1)]+1=2(-19-x)+2x+19 | | 81-4x=8x-21 | | y=-x^2(-20x)(-42) | | y=-x^2-20x-42 | | 3a=-9 | | 1+6(9-7x)-13x=-50x | | 3(8-2x)=-7x | | [-5.42]= | | 3b*1b=400 | | 6x+2x-5x-9+1=-5-2x+2 | | -2x=7x+7-5x-1-x+3x | | 7c+2=16 | | 3b*b+400=0 | | -2x=7x+7-5x-1-x | | 4x+4=7x-3+2+5+x |